Calculation of Talocrural Joint Axis Motion by Approximating Trochlea Tali with Conical Side Surface - Nomura, Kenta; Kosugi, Shinichi; Tanaka, Yasuhito; Takemura, Hiroshi (British Journal of Healthcare and Medical Research, 2017)
The motion of the talus, the most complex and important bone in ankle motion, is determined by the geometric characteristics of the articular surface of the talocrural joint, known as the trochlea tali. Therefore, modeling the geometric features of the trochlea tali is important for various fields. The purpose of this study is to approximate the rotation axis of the talocrural joint, which is important in the motion of the ankle foot with a conical model. In this experiment, a foot in four types of postures was photographed using computerized tomography (CT). An approximate cone was generated from point cloud data of the trochlea tali, obtained in this CT imaging experiment. In addition, the relationship between the rotation axis of the talus obtained by this experiment and the approximated cone was confirmed by this study. The results show that the axis of rotation of the talocrural joint moves along the side surface of the approximated cone, formed by two protruded shapes of trochlea tali. This suggests that the proposed method can be used to model the rotation axis of the talocrural joint with the side surface of the cone.